Clinical analysis of preoperative deep vein thrombosis risk factors in patients with colorectal cancer: Retrospective observational study. Issue 4 (29th April 2019) - Nakagawa, Kazuya; Watanabe, Jun; Suwa, Yusuke; Suzuki, Shinsuke; Ishibe, Atsushi; Ota, Mitsuyoshi; Kunisaki, Chikara; Endo, Itaru
Abstract: Aim: Deep vein thrombosis (DVT) is a major complication of cancer. The postoperative prevalence of DVT in colorectal cancer (CRC) surgery is high, but the preoperative prevalence and the risk factors have not been clarified in detail. The objective of this retrospective study was to investigate the preoperative prevalence and risk factors of DVT in patients admitted to hospital for CRC surgery. Methods: From January 2013 to March 2017, 1006 patients admitted for CRC surgery were deemed eligible for this retrospective study. Diagnosis of preoperative DVT was confirmed by compression ultrasonography. Prevalence of silent DVT in lower limbs in patients before CRC surgery was assessed, and the risk factors for preoperative DVT were investigated regarding the correlation of DVT with the patient's background. Results: Preoperative DVT and asymptomatic pulmonary thromboembolism were diagnosed in 136 (13.5%) and in 10 (1.0%) of 1006 patients overall, respectively. Multivariate analysis showed that increased age (≥75 years), female gender, and an elevatedd ‐dimer level (>1.0 μg/mL) were independent risk factors for preoperative DVT in this study. Notably, the prevalence of preoperative DVT exceeded 50% in patients with all three predictors. Conclusions: A high prevalence (13.5%) of preoperative DVT was found in patients admitted to the hospital for CRC surgery. The present results suggest that instrumental screening should be encouraged, at least in subgroups at a higher risk of preoperative DVT. Abstract : We retrospectively analyzed a total of 1006 patients who underwent elective colorectal resection. Preoperative deep vein thrombosis was diagnosed in 136 patients (13.5%). Multivariate analysis showed that increased age (≥75 years), female gender, and elevatedd ‐dimer levels (>1.0 μg/mL) were independent risk factors for preoperative deep vein thrombosis.